The Role of Makeup and Costume Artists in Creating a Theatrical Mise En Scene in the Fantasy Film Abracadabra - Nabilah, Zulfa Yasmin; Arifianto, Budi Dwi (Universitas Muhammadiyah Surakarta, 2023)
Abracadabra is a 2020 Indonesian fantasy comedy-drama film with a magic theme, directed by Faozan Rizal. The success of this movie lies not only in the interesting storyline but also in the ability to build a fantasy world that looks alive and charming through makeup and costumes. The movie won the best makeup and costume award at the Indonesian Film Festival (FFI). This research aims to identify the role of makeup and costume artists in creating theatrical mise en scene in the fantasy film Abracadabra. The method used in this research is descriptive-qualitative. Data collection techniques include interviews, documentation, and observation. This research uses three stages in analyzing data: data reduction, data display, and conclusion drawing. In testing the validity of the data, researchers used source triangulation, which means comparing and rechecking data from more than one source, to ascertain whether the data is correct or not. The results of this study show that in creating theatrical mise en scene, of course, there are things that are done by makeup and costume artists in the pre-production and post-production stages. Makeup and costume artists are responsible for all creative aspects, including designing the overall makeup and costume concept of the film. To create theatrical mise en scene through makeup and costumes, considerations are needed, such as the use of certain colors or designs to create a stage or theatrical impression, so it can be concluded that the role of makeup and costume artists is very important to create a fantasy world in accordance with the concept of the film Abracadabra and give the impression to the audience more intensely with the story presented.